Whole-exome sequencing reveals genomic landscape of intrahepatic cholangiocarcinoma and identifies SAV1 as a potential driver - Zheng-Jun Zhou; Yu-Hang Ye; Zhi-Qiang Hu; Yue-Ru Hou; Kai-Xuan Liu; Rong-Qi Sun; Peng-Cheng Wang; Chu-Bin Luo; Jia Li; Ji-Xue Zou; Jian Zhou; Jia Fan; et al. (Nature Communications, 2024)
Abstract Intrahepatic cholangiocarcinoma (ICC) is the second most common primary hepatic malignancy after hepatocellular carcinoma, with poor prognosis and limited treatment options. The genomic features of ICC in Chinese patients remain largely unknown. In this study, we perform deep whole-exome sequencing of 204 Chinese primary ICCs and characterize genomic alterations and clonal evolution, and reveal their associations with patient outcomes. We identify six mutational signatures, including Signatures A and F, which are highly similar to previously described signatures linked to aristolochic acid and aflatoxin exposures, respectively. We also identify 13 significantly mutated genes in the ICC samples, including SAV1. We find that SAV1 was mutated in 2.9% (20/672) of 672 ICC samples. SAV1 mutation is associated with lower SAV1 protein levels, higher rates of tumor recurrence, and shorter overall patient survival. Biofunctional investigations reveal a tumor-suppressor role of SAV1: its inactivation suppresses Hippo signaling, leading to YAP activation, thereby promoting tumor growth and metastasis. Collectively, our results delineate the genomic landscape of Chinese ICCs and identify SAV1 as a potential driver of ICC.